2013
DOI: 10.1002/j.0022-0337.2013.77.10.tb05609.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well–Being, Health, and Stress Sources in Turkish Dental Students

Abstract: This study investigated the psychological well-being and overall health of a group of Turkish dental students and their sources of stress. Two hundred and seventy-seven students (57 percent female) from Gazi University Dental Faculty completed the Dental Environment Stress (DES) questionnaire, the Psychological General Well-Being (PGWB) index, and the SF-36 Health Survey. The results showed that the DES scores increased over the ive-year period. Pressure to perform, faculty and administration, workload, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 27 publications
(65 reference statements)
7
70
5
8
Order By: Relevance
“…How a student responds to stressful situations depends on the clinical learning environment, for example student/teacher ratio, which varies between and even within countries. But this response also depends on the political context, such as government support and sociocultural environment, for example degree of competitiveness and communication in the academic hierarchy between students and teachers . Perceived stress also depends on individual characteristics, such as beliefs and attitudes .…”
Section: Discussionmentioning
confidence: 99%
“…How a student responds to stressful situations depends on the clinical learning environment, for example student/teacher ratio, which varies between and even within countries. But this response also depends on the political context, such as government support and sociocultural environment, for example degree of competitiveness and communication in the academic hierarchy between students and teachers . Perceived stress also depends on individual characteristics, such as beliefs and attitudes .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, female students had higher levels of stress than male counterparts in all stress domains except for "social stressors" domain. Many studies reported gender-related differences regarding DES (17,20,(37)(38)(39). Female students were more open to express stress issues than their male counterparts, and their response to stressors also differed.…”
Section: Discussionmentioning
confidence: 99%
“…Dental environment-induced stress can negatively affect students' well-being unless dealt with appropriately. Ultimately, the academic performance of these students will deteriorate (8,13). Stress can be very much expected among dental students not only because of their academic environment, but also because of their social and cultural background, which can provoke or modify stress among such students (14).…”
Section: Introductionmentioning
confidence: 99%
“…O perfil do estilo de vida do estudante que ingressa no ensino superior está relacionado à sua capacidade de adaptação a esta nova fase da vida como também foi observado por Costa e Leal 19 . Esta é considerada uma variável diretamente ligada às manifestações de estresse 20 . Neste estudo, todos os perfis encontrados mostraram comportamentos que podem contribuir como fatores estressores e, como consequência, causar o aparecimento de psicopatologias como a ansiedade e a depressão 21 , as quais são significativamente presentes entre graduandos da área da saúde 22 .…”
Section: Discussionunclassified